1991
DOI: 10.1152/ajprenal.1991.261.1.f197
|View full text |Cite
|
Sign up to set email alerts
|

Myo-inositol and betaine transporters regulated by tonicity are basolateral in MDCK cells

Abstract: Myo-inositol and glycinebetaine are compatible osmolytes accumulated in the renal medulla and in MDCK cells cultured in hypertonic media. Both osmolytes are taken up by MDCK cells on Na-coupled transporters. The maximal velocity (Vmax) of both cotransporters is increased by culture in hypertonic medium. When hypertonic MDCK cells are shifted to isotonic medium there is a large transient efflux of osmolytes. To determine the polarity of the cotransporters and the transient efflux, we grew MDCK cells on a porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
74
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 0 publications
4
74
1
Order By: Relevance
“…Glycine uptake was performed at room temperature according to a modification of the method of Yamauchi et al (29). After one wash of each chamber with complete phosphate-buffered saline (PBS/Ca/Mg: 137 mM NaCl, 2.7 mM KCl, 0.89 mM CaCl 2 , 0.49 mM MgCl 2 , 4.3 mM Na 2 HPO 4 ⅐7H 2 O, 1.4 mM KH 2 PO 4 , pH 7.3) and another wash with uptake buffer (150 mM NaCl, 5 mM KCl, 1 mM MgCl 2, 1 mM CaCl 2, 10 mM D(ϩ)-glucose, 10 mM HEPES-Tris, pH 7.4), the cells were incubated with 0.2 M [ 3 H]glycine in uptake buffer either in the upper or in the lower chamber for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Glycine uptake was performed at room temperature according to a modification of the method of Yamauchi et al (29). After one wash of each chamber with complete phosphate-buffered saline (PBS/Ca/Mg: 137 mM NaCl, 2.7 mM KCl, 0.89 mM CaCl 2 , 0.49 mM MgCl 2 , 4.3 mM Na 2 HPO 4 ⅐7H 2 O, 1.4 mM KH 2 PO 4 , pH 7.3) and another wash with uptake buffer (150 mM NaCl, 5 mM KCl, 1 mM MgCl 2, 1 mM CaCl 2, 10 mM D(ϩ)-glucose, 10 mM HEPES-Tris, pH 7.4), the cells were incubated with 0.2 M [ 3 H]glycine in uptake buffer either in the upper or in the lower chamber for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Like taurine, betaine accumulation by MDCK cells is primarily localized to the basolateral surface (20). Kinetic analysis reveals the presence of two distinct transport systems for betaine, a high-affinity system and a low-affinity system (20).…”
Section: Effect Of Other Osmolytes and Amino Acids On The Ability Of mentioning
confidence: 99%
“…The transporter was cloned from Madin-Darby canine kidney (MDCK) cells (1); BGT1 transport activity is low in MDCK cells maintained in isotonic medium but greatly induced in response to prolonged hypertonic stress. Transcription plays a major role in this stimulation, leading to increased BGT1 mRNA levels and consequently increased transport activity (1,2). However, it has been suggested that the post-transcriptional regulation of BGT1 protein also plays a role in cell adaptation to hypertonic stress (3).…”
mentioning
confidence: 99%